Spontaneous assembly of a self-complementary oligopeptide to form a stable macroscopic membrane. - Zhang, S (1993)
A 16-residue peptide [(Ala-Glu-Ala-Glu-Ala-Lys-Ala-Lys)2] has a characteristic beta-sheet circular dichroism spectrum in water. Upon the addition of salt, the peptide spontaneously assembles to form a macroscopic membrane. The membrane does not dissolve in heat or in acidic or alkaline solutions, nor does it dissolve upon addition of guanidine hydrochloride, SDS/urea, or a variety of proteolytic enzymes. Scanning EM reveals a network of interwoven filaments approximately 10-20 nm in diameter. An important component of the stability is probably due to formation of complementary ionic bonds between glutamic and lysine side chains. This phenomenon may be a model for studying the insoluble peptides found in certain neurological disorders. It may also have implications for biomaterials and origin-of-life research.